2014
DOI: 10.1111/cmi.12325
|View full text |Cite
|
Sign up to set email alerts
|

Targeting eukaryotic Rab proteins: a smart strategy for chlamydial survival and replication

Abstract: SummaryChlamydia, an obligate intracellular bacterium which passes its entire lifecycle within a membrane-bound vacuole called the inclusion, has evolved a variety of unique strategies to establish an advantageous intracellular niche for survival. This review highlights the mechanisms by which Chlamydia subverts vesicular transport in host cells, particularly by hijacking the master controllers of eukaryotic trafficking, the Rab proteins. A subset of Rabs and Rab interacting proteins that control the recycling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 61 publications
0
41
0
Order By: Relevance
“…RAB GTPases are master regulators of vesicle fusion and particular RABs are recruited to inclusions, some of them in a species-specific manner 53 . RAB1, RAB4, RAB11 and RAB14 were recruited to all of the species tested, whereas RAB6 was recruited only to C. trachomatis and RAB10 was recruited only to C. pneumoniae .…”
Section: Establishing An Intracellular Nichementioning
confidence: 99%
“…RAB GTPases are master regulators of vesicle fusion and particular RABs are recruited to inclusions, some of them in a species-specific manner 53 . RAB1, RAB4, RAB11 and RAB14 were recruited to all of the species tested, whereas RAB6 was recruited only to C. trachomatis and RAB10 was recruited only to C. pneumoniae .…”
Section: Establishing An Intracellular Nichementioning
confidence: 99%
“…trachomatis, as for many other intracellular pathogens, have developed different strategies to survive and replicate within infected cells. By recruiting certain Rabs and excluding others, these bacteria avoid degradation in the phagocytic pathway and intercept vesicles carrying host molecules required for bacterial growth (Damiani et al, 2014;Gutierrez, 2013). Although several researchers have explored the participation of Rabs in chlamydial infection, this issue is far from being fully understood.…”
Section: Rab39a Localization To Chlamydial Inclusionsmentioning
confidence: 99%
“…Inclusion growth and bacterial replication depends on the acquisition of nutrients and biosynthetic constituents from the host. Following multiple rounds of replication, reticulate bodies redifferentiate back into elementary bodies and leave infected cells by lysis or extrusion, after which bacteria disseminate and invade neighbouring cells (Bastidas et al, 2013;Damiani et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…One family of secreted proteins is the inclusion proteins (Incs) which are anchored by their transmembrane domain in the inclusion membrane. It was shown that Incs can specifically interact with transport vesicles through interaction with Rab and Syntaxin proteins (Damiani et al 2014). Furthermore, a specific interaction of IncG with the host cell protein 14-3-3β was shown (Scidmore and Hackstadt 2001).…”
Section: Enrichment Of Anti-apoptotic Proteinsmentioning
confidence: 98%